Using Visuals and Manipulative for Supporting ELS - Ali Ghafil Harbi (Peerian Journals Publishing, 2024)
One effective way to support English Language Learners (ELLs) is through the use of visuals and manipulatives in the classroom. Visual aids can play a significant role in helping ELLs comprehend and retain new information, as they provide concrete and relatable illustrations of abstract concepts. Meanwhile, manipulatives, such as flashcards, objects, or interactive games, offer a hands-on approach that can enhance ELLs' engagement and understanding of language and content. Visuals, including posters, charts, diagrams, and multimedia resources, provide ELLs with a visual representation of the language being taught. This can be particularly beneficial when introducing vocabulary, grammar concepts, or explaining complex instructions. Using visual aids not only makes the content more comprehensible but also creates a more inclusive learning environment, accommodating various learning styles and linguistic abilities. Similarly, incorporating manipulatives into language learning can make abstract language concepts more tangible and understandable for ELLs. For instance, using flashcards with words and corresponding images can help build associations between the two, aiding in vocabulary acquisition. Interactive games and activities provide opportunities for ELLs to practice language in a fun and engaging manner, allowing them to internalize language patterns and structures more effectively. In conclusion, utilizing visuals and manipulatives in the classroom can greatly support ELLs in their language acquisition journey. By making use of these tools, educators can create a more immersive and interactive learning experience that caters to the diverse needs of ELLs, ultimately fostering a more supportive and effective language learning environment
Keywords: Visuals; Manipulatives; ELLs; English Language Learners